(untitled) (Research, Society and Development, 2022)
Sexual Education is in the National Curriculum Parameters (PCNs), and proposes that when ministering on sexual education, one seeks to inform and problematize issues related to sexuality from the experience, beliefs and values of the students, to expand the information and thus raise questions about the most appropriate choices for each one. However, in order to achieve this objective, it is necessary that the teacher is prepared for this theme and for the appropriate situations that may arise in the classroom with their students. Therefore, the objective of this work was to understand the teacher’s perceptions about sex education, as well as the challenges and facilities arising from the school context. The research was carried out in two schools in the municipality of Foz do Iguaçu - PR, and data collection took place through a semi-structured interview with six teachers who voluntarily volunteered to participate in the research. The results show that there is a large gap in the work on sex education and there is a lack of training for teachers, generating fear and insecurity when talking about sexuality, and there is still a lack of didactic support materials on the subject, to facilitate the study and make the interactive and dynamic learning. With this, it is possible to understand that the PCNs proposal does not contemplate the reality studied, so new perspectives on legislation and practice are suggested so that in fact, a sex education based on humanity and information that instrumentalizes and provide security for the teacher to the address the matter.